2003
DOI: 10.2166/wst.2003.0246
|View full text |Cite
|
Sign up to set email alerts
|

A method for the numerical assessment of sediment interceptors

Abstract: The problems associated with the presence of sediments in sewers and stormwater drainage systems represent a major engineering challenge. Their accumulation can result in operational difficulties, including low restriction and premature overflows. Sediments themselves are known to contribute significantly to the polluting load of storm overflows. The use of sediment interceptors within sewer systems or downstream of stormwater intakes represents one way of alleviating these problems. A study of stormwater sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 2 publications
(1 reference statement)
0
11
0
Order By: Relevance
“…In the current numerical experiment an efficiency, E, and a revised efficiency, RE, have been defined. E is defined in the same manner chosen by Faram et al (2003) and Stovin and Saul (1996), where E ¼ðparticles trapped þ particles retainedÞ =ðparticles introducedÞ:…”
Section: Methodsmentioning
confidence: 99%
“…In the current numerical experiment an efficiency, E, and a revised efficiency, RE, have been defined. E is defined in the same manner chosen by Faram et al (2003) and Stovin and Saul (1996), where E ¼ðparticles trapped þ particles retainedÞ =ðparticles introducedÞ:…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity of the DPM to the particle injection location was established by injecting particles at different horizontal segments which were named top, centre and bottom (depending upon their vertical locations) and inside, middle and outside (depending upon their horizontal locations). Apart from the location of the particles, various other authors [24,25,26,28] have also suggested that a large number of particles need to be injected in order to mute the effect of random variations and to obtain representative particle fates. Thus, a minimum of 5000 particles were injected for each set of simulations.…”
Section: Effect Of Particle Injection Locationmentioning
confidence: 99%
“…Studies by Egarr et al [27] have also investigated the importance of different shape factors used in drag calculations in the DPM model and their effect on particle trajectory calculations. The ability of the DPM to provide reliable outputs for industrial applications has been demonstrated by Faram and Harwood [28] on sediment interceptors and Jayanti and Narayanan [29] on sedimentation tanks.…”
Section: Introductionmentioning
confidence: 99%
“…However, the latter modelled a sump with a horizontal inlet, which results should not have been extrapolated to gully pots with a vertical impinging jet. Faram and Harwood [17] also modelled the removal efficiency of gully pots and validated the results with a few physical tests of the removal efficiency; no validation of the velocity fields was reported.…”
Section: Introductionmentioning
confidence: 99%